The Interplay Between Programmed Death Ligand 1 and Vimentin in Advanced Non-Small-Cell Lung Cancer - Bronte, Giuseppe; Puccetti, Maurizio; Petracci, Elisabetta; Landi, Lorenza; Cravero, Paola; Scodes, Simona; Ulivi, Paola; Ravaioli, Sara; Tumedei, Maria Maddalena; Burgio, Marco Angelo; Cappuzzo, Federico; Delmonte, Angelo; et al. (Frontiers in Oncology, 2021)
BACKGROUND: Current therapy for non-small-cell lung cancer (NSCLC) frequently includes immune checkpoint inhibitors, such as pembrolizumab, and programmed death ligand 1 (PD-L1) positivity is mandatory for its use in this setting. Vimentin plays a role in carcinogenesis through the activation of the epithelial-to-mesenchymal transition (EMT) process. Its prognostic impact in NSCLC has been investigated in numerous studies but little data are available on its relation with PD-L1 expression. PATIENTS AND METHODS: We retrospectively retrieved data on patients with advanced NSCLC consecutively enrolled in a clinical trial at our institute. PD-L1 and vimentin expression were determined by immunohistochemistry. Correlations between variables were assessed using the Spearman correlation coefficient. The Kaplan-Meier method was used to estimate overall survival (OS) and the Log-rank test was used to compare survival curves. The association between demographic, clinical and biomarker information and survival was investigated with the Cox model. RESULTS: Fifty-three patients were included in the study. A weak positive correlation was observed between the PD-L1 and vimentin (ρ=0.41, P=0.003). Patients with PD-L1 values <1% showed a slightly better OS than those with higher values (HR=2.07; 95% CI: 0.92–4.65), but the difference was not significant (P=0.080). No difference in overall survival (OS) was observed on the basis of vimentin expression (HR=1.25; 95% CI: 0.59–2.66; P=0.554). Patients harboring both vimentin and PD-L1 negative expression (<1%) showed a trend towards better survival than those with ≥1% expression (HR=2.31; 95% CI: 0.87-6.17, P=0.093). No significant associations were observed between gender, age at diagnosis, stage at diagnosis, histology, KRAS or EGFR status, radical surgery or immunotherapy and OS. CONCLUSIONS: The weak positive association between PD-L1 and vimentin suggests a potential interplay between these biomarkers. Further research is warranted to evaluate EMT and immune escape as two components of the same process.